2020
DOI: 10.1177/0093854819896385
|View full text |Cite
|
Sign up to set email alerts
|

Offending Histories and Typologies of Suspected Sexual Offenders Identified Via Untested Sexual Assault Kits

Abstract: In this study, we present findings that detail the criminal offending histories and typologies of suspected sexual offenders identified from an initiative to follow up on the testing of thousands of previously untested sexual assault kits (SAKs). This study advances our understanding of sexual offenders by incorporating data from criminal justice system records (“detected” criminal offending) with data from newly tested SAKs that were not previously adjudicated (“undetected” sexual offending). Our findings dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
(45 reference statements)
1
25
0
Order By: Relevance
“…The incremental cost‐effectiveness analyses showed that investigating all cases instead of only those with CODIS hits meant paying $9121 p/additional indictment and $12,000 p/additional conviction. Given the $241,960 tangible and intangible societal cost for each sexual assault, this is a relatively small price for the system to expend to get dangerous sexual offenders [40] off the streets, give justice to victims [43], and make the community safer [40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incremental cost‐effectiveness analyses showed that investigating all cases instead of only those with CODIS hits meant paying $9121 p/additional indictment and $12,000 p/additional conviction. Given the $241,960 tangible and intangible societal cost for each sexual assault, this is a relatively small price for the system to expend to get dangerous sexual offenders [40] off the streets, give justice to victims [43], and make the community safer [40].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the cost‐effectiveness did not come from the testing (which will always be a cost to the system) but from the investigative follow‐up. Specifically, the cost savings occurred from what transpired after the testing—the indictments and convictions that got dangerous sexual offenders off the streets, thereby preventing future sexual assaults (in addition to other crimes see [40]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the lack of universal testing of SAKs, stakeholders argue that previously unsubmitted SAKs may still hold evidentiary value. More specifically, if now tested, they may lead to the arrest and prosecution of offenders, and especially those offenders who have committed multiple crimes (Lovell et al, 2020). Comparing samples from these unsubmitted kits to samples in state and federal DNA databases would expose such offenders who would otherwise have remained hidden.…”
Section: Introductionmentioning
confidence: 99%
“…These high rates of case attrition deny justice for victims and prevent individuals charged with sexual offenses from being held accountable (Lovell et al, 2020). Accordingly, it is critical for officers to receive training aimed at reducing adherence to rape myths, minimizing secondary trauma, and improving victim engagement with the criminal justice system (O’Neal, 2019).…”
mentioning
confidence: 99%